The relationship between mathematical attitudes and procrastination in learning exponential concepts - Lutfiyah Maharani; Dina Fakhriyana (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This study examines the relationship between students' attitudes toward mathematics, procrastination habits, and their mastery of NCTM's basic mathematical abilities in exponential material. Using a quantitative correlational approach, the research employed saturated sampling with 34 eighth-grade students from MTs Islamic Center as both sample and population. Data were collected via a mathematics attitude questionnaire, a procrastination questionnaire, and an NCTM-based math test, then analyzed using IBM SPSS Statistics 25 and Microsoft Excel. Results indicated: (1) a significant positive correlation (r = 0.730, R² = 53.2%) between mathematics attitude and NCTM ability mastery; (2) a significant negative correlation (r = -0.568, R² = 32.3%) between procrastination and NCTM mastery; and (3) a combined correlation (r = -0.485, R² = 59.2%) between both factors and NCTM ability. Theoretically, this study enriches understanding of affective influences—motivation and anxiety—on math learning. Practically, it highlights the need for teaching strategies that address students' emotional needs, such as contextual and participatory approaches, aligning with NCTM standards for fostering conceptual understanding and problem-solving skills. These findings emphasize improving math attitudes and reducing procrastination to enhance foundational competencies in exponential functions. Additionally, this research provides empirical evidence supporting the integration of psychological and pedagogical interventions in mathematics education to optimize learning outcomes.